Clinical heterogeneity of hyperornithinemia-hyperammonemia-homocitrullinuria syndrome in thirteen palestinian patients and report of a novel variant in the SLC25A15 gene - Dweikat, Imad; Khalaf-Nazzal, Reham (Frontiers in Genetics, 2022)
Background: Hyperornithinemia-Hyperammonemia-Homocitrullinuria (HHH) syndrome, is a rare autosomal recessive disorder characterized by impaired ornithine transport across the inner mitochondrial membrane. HHH is caused by biallelic disease-causing variants in the SLC25A15 gene. The clinical presentation of HHH is highly variable ranging from severe neonatal encephalopathy and hepatic failure to a milder form with corresponding learning difficulties. Methods: In this study, data from thirteen patients with HHH syndrome, diagnosed between the age of 1 week to 29 years at two tertiary care centers in Palestine, is presented. The clinical, biochemical, and molecular data are reviewed. Results: Analysis of the SLC25A15 gene sequence revealed a novel homozygous frameshift deletion in exon 5, NM_014252.4:c.552-555delTTTC; p.(Phe185SerfsTer8) in nine patients. The remaining four patients had a recurrent homozygous frameshift variant; NM_014252.4:c.446delG, (p.Ser149ThrfsTer45). The major acute clinical presentation found was encephalopathy and liver dysfunction. Nervous system involvement was common, progressive, and presented with signs of upper motor neuron disease as well as variable degrees of cognitive impairment. One patient had an initial presentation in adulthood with acute encephalopathy that responded well to treatment. There was no clear genotype-phenotype correlation. Conclusions: Our results confirm the marked clinical heterogeneity of HHH including severe neonatal presentation, hepatic failure, and progressive pyramidal tract dysfunction in all age groups. The disease progression was variable, even in patients with the same genetic variant, and in patients with severe neonatal-onset hepatic encephalopathy. We report a novel pathogenic variant in the SLC25A15 gene, further expanding the molecular spectrum of the disease.